Common warts and molluscum contagiosum: clinical evaluation of a nutraceutical associated with topical treatment - Fai, D.; Pellé, S.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
The body's immune reaction influences the natural history of warts and molluscum contagiosum, justifying the numerous attempts carried out so far of topical and systemic immune stimulation in the therapy of these viral proliferations. In this paper we report our experience in the use of a nutraceutical (Immunoskin plus ®) aimed at strengthening the immune system. The nutraceutical was used in association with traditional topical therapy in 30 children aged between 2 and 6 years with common warts and molluscum contagiosum. The results in this group were compared with those obtained with the sole conventional topical therapy in another group of 30 children suffering from warts and molluscum contagiosum. In the first group (Immunoskinplus associated with conventional topical therapy) recovered after 6 months 19/30 children; in the second group (only traditional therapy) healed in the same period of time 11/30 children.